Impact of vaccine economic programs on physician referral of children to public vaccine clinics: a pre-post comparison - Troy Judith A; Bardenheier Barbara; Janosky Janine E; Tabbarah Melissa; Zimmerman Richard K; Jewell Ilene K; Yawn Barbara P (BMC, 2006)
Abstract Background The Vaccines for Children (VFC) Program is a major vaccine entitlement program with limited long-term evaluation. The objectives of this study are to evaluate the effect of VFC on physician reported referral of children to public health clinics and on doses administered in the public sector. Methods Minnesota and Pennsylvania primary care physicians (n = 164), completed surveys before (e.g., 1993) and after (2003) VFC, rating their likelihood on a scale of 0 (very unlikely) to 10 (very likely) of referring a child to the health department for immunization. Results The percentage of respondents likely to refer was 60% for an uninsured child, 14% for a child with Medicaid, and 3% for a child with insurance that pays for immunization. Half (55%) of the physicians who did not participate in VFC were likely to refer a Medicaid-insured child, as compared with 6% of those who participated (P < 0.001). Physician likelihood to refer an uninsured child for vaccination, measured on a scale of 0 to 10 where 10 is very likely, decreased by a mean difference of 1.9 (P < 0.001) from pre- to post-VFC. The likelihood to refer a Medicaid-insured child decreased by a mean of 1.2 (P = 0.001). Conclusion Reported out-referral to public clinics decreased over time. In light of increasing immunizations rates, this suggests that more vaccines were being administered in private provider offices.